Kekuatan Aliansi Sebagai Dasar Ekskalasi Pertumbuhan Gereja Berdasarkan Kisah Para Rasul 2:46-47 - Janes Sinaga; Rudolf Weindra Sagala; Rolyana Ferinia; Stimson Hutagalung (Integritas: Jurnal Teologi, 2021)
Church growth is sometimes experienced very slowly in one congregation and this is due to several influencing factors including the reluctance of church members to be involved in worship services. For this reason, the author examines and explains why a Christian must serve and what services can be done in church worship. The purpose of this study is to understand the correct concept of the importance of the involvement of church members in worship services, where such involvement can be the strength of the existence of the church and the growth of the church. To get a complete explanation, the author uses qualitative research methods and uses literature studies from various bibliography lists, both books and journals and is supported by biblical verses so that they get a complete understanding. Through this research produce steps that must be taken by a Christian to be involved in worship services such as prayer services, word ministries, music services and hymns. It is hoped that this will increase the strength of the alliance as a basis for escalating church growth.